2017
DOI: 10.3389/fpsyt.2017.00222
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder: An Immunological Disorder?

Abstract: Patients with posttraumatic stress disorder (PTSD) exhibit an increased state of inflammation. Various animal models for PTSD have shown some of the same immune imbalances as have been shown in human subjects with PTSD, and some of these studies are discussed in this review. However, animal studies can only indirectly implicate immune involvement in PTSD in humans. This review of mainly studies with human subjects focuses on dissecting the immunological role in the pathogenesis of PTSD following initial trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 85 publications
6
48
1
4
Order By: Relevance
“…41,42 Finally, the HLA-B complex may be related through the known role of immunity and inflammation in stress-related disorders. 43,44 Extensive follow-up work is needed to determine the function of identified genes and their relationship to putative pathological processes. For example, in SCZ the MHC locus is now thought to influence risk through pruning of synapses using immune machinery rather than through classical immune pathways.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Finally, the HLA-B complex may be related through the known role of immunity and inflammation in stress-related disorders. 43,44 Extensive follow-up work is needed to determine the function of identified genes and their relationship to putative pathological processes. For example, in SCZ the MHC locus is now thought to influence risk through pruning of synapses using immune machinery rather than through classical immune pathways.…”
Section: Discussionmentioning
confidence: 99%
“…9 The prevalence of lifetime PTSD in the general US population is estimated to be between 6.1% and 8.3%. 12 Several studies have identified PTSD as a risk factor for cardiometabolic diseases as well as a predictor of poor outcomes in comorbid conditions such as acute myocardial infarction, asthma, and cancer. 12 Several studies have identified PTSD as a risk factor for cardiometabolic diseases as well as a predictor of poor outcomes in comorbid conditions such as acute myocardial infarction, asthma, and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 PTSD has been postulated to be associated with modification of stress response in the body as well as causing a pro-inflammatory state. 12 Several studies have identified PTSD as a risk factor for cardiometabolic diseases as well as a predictor of poor outcomes in comorbid conditions such as acute myocardial infarction, asthma, and cancer. [13][14][15][16][17] PTSD has also been shown to be associated with other psychiatric comorbidities (depression, anxiety), substance abuse, and noncompliance with medications and follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to other psychiatric disorders that exhibit increased plasma levels of both cortisol and pro-inflammatory cytokines suggesting possible glucocorticoid (GC) resistance, PTSD is associated with enhanced GR sensitivity and inflammation (Hoge et al, 2009;Neigh and Ali, 2016;Wang et al, 2017). Although GC are well known for their anti-inflammatory properties, there are also accounts of the pro-inflammatory effects of GCs (Cruz-Topete and Cidlowski, 2015;Desmet and De Bosscher, 2017), where low dose glucocorticoids are associated with enhanced inflammatory responses and high doses are anti-inflammatory.…”
Section: Introductionmentioning
confidence: 99%